Regulating Histone Deacetylase Signaling Pathways of Myeloid-Derived Suppressor Cells Enhanced T Cell-Based Immunotherapy - Adeshakin, Adeleye O.; Adeshakin, Funmilayo O.; Yan, Dehong; Wan, Xiaochun (Frontiers in Immunology, 2022)
Immunotherapy has emerged as a promising approach to combat immunosuppressive tumor microenvironment (TME) for improved cancer treatment. FDA approval for the clinical use of programmed death receptor 1/programmed death-ligand 1 (PD-1/PD-L1) inhibitors revolutionized T cell-based immunotherapy. Although only a few cancer patients respond to this treatment due to several factors including the accumulation of immunosuppressive cells in the TME. Several immunosuppressive cells within the TME such as regulatory T cells, myeloid cells, and cancer-associated fibroblast inhibit the activation and function of T cells to promote tumor progression. The roles of epigenetic modifiers such as histone deacetylase (HDAC) in cancer have long been investigated but little is known about their impact on immune cells. Recent studies showed inhibiting HDAC expression on myeloid-derived suppressor cells (MDSCs) promoted their differentiation to less suppressive cells and reduced their immunosuppressive effect in the TME. HDAC inhibitors upregulated PD-1 or PD-L1 expression level on tumor or immune cells sensitizing tumor-bearing mice to anti-PD-1/PD-L1 antibodies. Herein we discuss how inhibiting HDAC expression on MDSCs could circumvent drawbacks to immune checkpoint inhibitors and improve cancer immunotherapy. Furthermore, we highlighted current challenges and future perspectives of HDAC inhibitors in regulating MDSCs function for effective cancer immunotherapy.